Comparison and selection of light-emitting diodes (LEDs) for disease assays on plant pathogenic viruses and bacteria in greenhouses - Anne K. J. Giesbers; Barendinus J. A. van Doorn; Joanieke van Oorspronk; Carla Oplaat; Christel de Krom; Maria Bergsma-Vlami; Annelien Roenhorst (PLoS ONE, 2025)
Supplemental lighting in greenhouses has traditionally been dominated by high-pressure sodium (HPS) lights. However, a shift towards light-emitting diode (LED) technology is gaining momentum due to its energy efficiency, customizable light spectra, and adjustable light intensity, which together allow for more precise control over plant development. In plant pathogen diagnostics, where symptom expression is essential, HPS lights have typically been used in greenhouse settings. Since LEDs are generally optimized to promote plant growth and quality, they may affect plant physiology, including responses to pathogens. To investigate how different lighting sources affect the expression of viral and bacterial disease symptoms, two types of LEDs with different spectra were compared with the traditionally used HPS lights. LEDs with a “daylight” spectrum, featuring pronounced blue and red peaks resulted in poor virus symptom expression, though the expression of bacterial symptoms was less affected. In contrast, LEDs with a broad spectrum – characterized by a modest blue peak, a prominent red peak, and a small far-red peak – elicited virus and bacterial symptoms similar to those observed under HPS lights, when adjusted at equal light intensity level. This study provides insights into symptom development in plants inoculated with viruses and bacteria under various lighting conditions, highlighting the influence of light intensity and spectrum. Based on the results of this comparative study, “broad spectrum with far-red” LEDs were identified that are suitable for disease assays on plant pathogenic viruses and bacteria.